Finger clubbing in inflammatory bowel disease: association with upper small bowel lesions and need of surgery in Crohn's disease. Issue 6 (29th October 2020) - Romeo, Samanta; Neri, Benedetto; Mossa, Michelangela; Calabrese, Emma; Lolli, Elisabetta; Sena, Giorgia; Gesuale, Cristina; Chiaramonte, Carlo; Biancone, Livia
Abstract : Objective: Finger clubbing has been associated with inflammatory bowel disease (IBD). Aims: In a prospective single-center study, we aimed to assess the frequency of finger clubbing in a cohort of IBD patients. Whether finger clubbing is associated with clinical characteristics of IBD was also investigated. Methods: IBD patients with a detailed clinical history were enrolled. Finger clubbing was assessed by visual inspection. Data were expressed as median (range), chi-square, t -test. Multivariate logistic regression analysis was used to assess risk factors for finger clubbing, when considering demographic and clinical characteristics, smoking habits and chronic pulmonary diseases (CPD). Results: Finger clubbing was searched in 470 IBD patients: 267 Crohn's disease and 203 ulcerative colitis. Finger clubbing was more frequent in Crohn's disease than in ulcerative colitis: 45/267 (16.8%) vs. 15/203 (7.3%) [odds ratio (OR), 2.54 (1.37–4.70); P  = 0.003]. Crohn's disease involved the ileum (59.9%), colon (4.5%), ileum-colon (25.8%) and upper gastrointestinal (GI) (9.8%). Ulcerative colitis extent included proctitis (E1) (13.4%), left-sided (E2) (43.3%) and pancolitis (E3) (43.3%). Upper GI lesions, but not other Crohn's disease localizations, were more frequent in patients with finger clubbing [9/45 (20%) vs. 17/222 (7.7%); P  = 0.032]. Crohn's disease-related surgery was more frequent in patients with finger clubbing [36/45 (80%) vs. 107/222 (48.1%); P  < 0.001]. In Crohn's disease, the only risk factors for finger clubbing were upper GI lesions and Crohn's disease-related surgery [OR, 2.58 (1.03–6.46), P  = 0.04; OR, 4.07 (1.86–8.91), P  = 0.006]. Ulcerative colitis extent was not associated with finger clubbing [E1: OR, 0.27 (0.02–3.44), P  = 0.33; E2: OR, 0.93 (0.24–3.60), P  = 0.92; E3:OR, 0.64 (0.22–1.86), P  = 0.59]. In ulcerative colitis, but not in Crohn's disease, finger clubbing was more frequent in smokers [13/15 (86.6%) vs. 99/188 (52.6%); P  = 0.01] and in patients with CPD [5/15 (33.3%) vs. 16/188 (8.5%); P  = 0.002]. Smoking and CPD were the only risk factors for finger clubbing in ulcerative colitis [OR, 7.18 (1.44–35.78), P  = 0.01; OR, 10.93 (2.51–47.45), P  = 0.001]. Conclusion: In the tested IBD population, finger clubbing was more frequent in Crohn's disease than in ulcerative colitis. In Crohn's disease, upper GI lesions and history of Crohn's disease-related surgery were risk factors for finger clubbing, suggesting the possible role of finger clubbing as a subclinical marker of Crohn's disease severity.